State-owned enterprises, market competition and the boundaries of competition law in Malaysia - Ahamat, Haniff; Abdul Rahman, Nasarudin (UKM Press, 2017)
This article examines the challenges and opportunities of subjecting Malaysian State-Owned Enterprises (SOEs) to its main competition legislation that is the Competition Act 2010. This article first highlights the nature of economic activities which is a crucial element in determining that an SOE actually participates in the market. Despite the contentions that SOEs have a unique character, and should be excluded from normal regulation of competition, this article argues that competition law is important in addressing the problems brought about by Government or State’s involvements in businesses. This article finds that while the Competition Act 2010 does not apply a blanket exemption to SOEs, there are many hurdles in applying the law to them. Based on the literature analysis in the earlier part of this article, this article finds that some of these hurdles are justified especially if they are connected to the notion of natural monopoly. Where there are not connected, extending the check and balance mechanisms against the market activities of the SOEs will be crucial. This article shows that the avenues to realise it still exist but are limited.